2001
DOI: 10.1063/1.1355995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation on the thermoelectric properties of PbTe and PbS epitaxial films

Abstract: We report on the thickness d dependences of the Seebeck coefficient, electrical conductivity, and Hall coefficient of PbTe and PbS epitaxial thin films (d=5–200 nm), prepared by thermal evaporation in vacuum and deposition on (001) KCl substrates. The oxidation of the films in air at 300 K leads to a sign inversion of the carrier type from n to p in films with d⩽125 and 110 nm for PbTe and PbS, respectively. The observed d dependences are interpreted in terms of compensating acceptor states created by oxygen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…The higher the figure of merit of a material, the more efficiently it can generate electricity from heat. PbTe is an important thermoelectric material [4][5][6][7][8][9][10][11][12][13][14] due to its high figure of merit, good chemical stability, low vapor pressure and high melting point (∼900 K). PbTe is IV-VI compound semiconductor, with the rock salt structure and a narrow band gap (E g = 0.29 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the figure of merit of a material, the more efficiently it can generate electricity from heat. PbTe is an important thermoelectric material [4][5][6][7][8][9][10][11][12][13][14] due to its high figure of merit, good chemical stability, low vapor pressure and high melting point (∼900 K). PbTe is IV-VI compound semiconductor, with the rock salt structure and a narrow band gap (E g = 0.29 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The more detailed (compare to Ref. 18) studies of the galvanomagnetic and thermoelectric properties as a function of d that were conducted in the present work allowed us to reveal an extremum behavior of the (d) and (d) dependences in the p region, which we attribute to the transition from a semicontinuous film to a continuous one. It follows from our data that as a result of oxidation in very thin PbSe films, the maximum possible concentrations of p-type charge carriers, which are usually attained in bulk PbSe due to doping (ϳ2 и 10 20 cm Ϫ3 ), can be obtained in thin films through the oxidation mechanism.…”
Section: Resultsmentioning
confidence: 93%
“…18, we reported the d dependences of the thermoelectric properties in PbTe and PbS thin films prepared by the thermal evaporation of the corresponding crystalline material in a vacuum and its subsequent deposition onto (001) KCl substrates. It was shown that the oxidation of the films in air at 300 K leads to a sign inversion of the carrier type from n-type to p-type in films with d Յ 125 nm and d Յ 110 nm for PbTe and PbS, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the investigated object is the ntype condensate, this problem can be solved by film coating protective layer EuS. The authors of [6] have shown that EuS thickness ~30 nm is quite enough to completely avoid the oxygen action. Thus, this protective layer is regarded as one of barriers that creates a quantum well for carriers in PbTe structure.…”
Section: Introductionmentioning
confidence: 99%